Processing of pHEMA/TiO2 based nanocomposites used as an excellent dental materials. (2022) - Alamgir, Md.; Shahabuddin, Syed; Mallick, Ashis; Nayak, G.C.
Abstract: In this study, a poly(hydroxyethyl methacrylate) (pHEMA) network was prepared using hydroxyethyl methacrylate (HEMA) as a foundation material and trimethylolpropane trimethacrylate (TMPTA) and benzoyl peroxide (BPO) as cross-linking agents. The pHEMA nanocomposites were prepared by the melt processing method. In this method, a twin-screw extruder machine was used. Twin-screw extrusion is used largely for mixing, compounding, or reacting polymeric materials. The flexibility of twin- screw extrusion equipment allows this operation to be designed specifically for the formulation being processed. The nanocomposites of pHEMA/1wt%TiO2 and pHEMA/2wt%TiO2 were manufactured employing pHEMA as a matrix with the buildup of lesser quantities of titanium oxide nanoparticles TiO2 1 wt% and 2 wt% as reinforcement materials. The mechanical properties investigation of pHEMA/1wt%TiO2 and pHEMA/2wt%TiO2 nanocomposites was carried out via Multi-cyclic Indentation and Micro-scratch analysis. The microstructural analysis of the nanocomposites was studied by FESEM analysis. Important changes in microstructural behaviour with improved mechanical effects were observed in pHEMA/1wt%TiO2 and pHEMA/2wt%TiO2 nanocomposites as compared to pure pHEMA. In this work, real pHEMA and pHEMA/1wt%TiO2 and pHEMA/2wt%TiO2 nanocomposites were examined for dental applications.